Alcohol Consumption by workers in automobile repair shops of a slum of Kolkata: An assessment with AUDIT instrument - Dasgupta, A; Ray, S; Pal, J; Biswas, R; Ray, D; Ghosal, A (Nepal Journal of Epidemiology, 2013)
Background National Household Survey of Drug Use in the India in its systematic effort to document the nationwide prevalence of drug use including alcohol consumption reported that almost 21% of the adult male Indian consume alcohol in a year. To find out prevalence, pattern and consequences of drinking and determine the relationship of alcohol use with demographic and socio-economic factors among auto-mobile repair workers. Materials and Methods A cross-sectional study was conducted among auto-mobile repair workers in the urban field practice area of All India Institute of Hygiene and Public Health, Kolkata. Results Prevalence of alcoholism in the community of automobile repair workers was found to be as high as 79%. More than 50% of the alcoholics belonged to the hazardous and dependent variety according to the WHO developed AUDIT instrument.53.01% of the alcoholics consumed foreign liquor predominantly and 87.95% bought them from licensed liquor shops. Mean age of initiation of drinking was 18.67 years. Taking loan OR (95% CI) 3.51(1.56-7.92), gambling OR (95% CI) 3.38(1.48-7.69) and clinical signs of alcoholism OR (95% CI) 5.52 (2.13 - 14.29) were significantly associated with chronic alcohol abuse. A multivariate logistic regression model was created for socio-economic variables which showed education AOR (95%CI) 4.65(1.34- 16.31) and total number of family members AOR (95%CI) 5.33(1.31-25.02) were significantly associated with drinking status (Nagelkerke R2 for this model is 0.2585). Conclusion The prevalence of alcoholism is high in the automobile repair workers and therefore all efforts must be made to reduce, if not eliminate, alcohol consumption among the workers of auto-mobile service centres. DOI: http://dx.doi.org/10.3126/nje.v3i3.9188 Nepal Journal of Epidemiology 2013;3(3): 269-274